2018
DOI: 10.1186/s40249-018-0452-1
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of epilepsy in onchocerciasis endemic health areas in Democratic Republic of the Congo

Abstract: BackgroundA high prevalence of epilepsy has been observed in many onchocerciasis endemic regions. This study is to estimate the prevalence of active epilepsy and exposure to Onchocerca volvulus infection in a rural population in Ituri province, Democratic Republic of Congo.MethodsIn August 2016, a community-based cross-sectional study was conducted in an onchocerciasis endemic area in the rural health zone of Logo, Ituri Province. Households within two neighbouring health areas were randomly sampled. To identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 21 publications
2
55
1
Order By: Relevance
“…More recent studies have reported nodding seizures among persons with epilepsy (PWE) in the onchocerciasis-endemic regions in Cameroon [10] and the Democratic Republic of Congo [11]. A high prevalence of epilepsy has also been reported in many onchocerciasis meso-and hyper-endemic regions [12][13][14][15] particularly where transmission is poorly controlled [16][17][18][19]. A study in an onchocerciasis-endemic region in the Mbam valley in Cameroon showed that the risk of developing epilepsy increased with increasing O. volvulus microfilarial density [20].…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have reported nodding seizures among persons with epilepsy (PWE) in the onchocerciasis-endemic regions in Cameroon [10] and the Democratic Republic of Congo [11]. A high prevalence of epilepsy has also been reported in many onchocerciasis meso-and hyper-endemic regions [12][13][14][15] particularly where transmission is poorly controlled [16][17][18][19]. A study in an onchocerciasis-endemic region in the Mbam valley in Cameroon showed that the risk of developing epilepsy increased with increasing O. volvulus microfilarial density [20].…”
Section: Introductionmentioning
confidence: 99%
“…Onchocerciasis‐associated epilepsy (OAE) and the nodding syndrome, an epileptic condition which affects children living in areas where onchocerciasis is endemic, are important entities …”
Section: Treatmentmentioning
confidence: 99%
“…Therefore, we initially performed a four months proof-of-concept trial to investigate the effect of ivermectin on the frequency of seizures in OIPWE treated with phenobarbital. The trial was performed in the Logo health zone, an onchocerciasis-endemic area with a high epilepsy prevalence (4.6%) in the Ituri province in the Democratic Republic of Congo (DRC), where ivermectin had never been distributed previously [7]. Between October and November 2017, a community-based treatment of epilepsy was initiated and 387 persons with confirmed epilepsy (PWE) were enrolled in the program.…”
Section: Introductionmentioning
confidence: 99%